Reproductive Biology of Frigate Tuna (Auxis thazard Lacepède, 1800) Caught by Fishermen in West Sumatra Waters - Nofrita, Nofrita; Nurdin, Jabang; Bintari, Andhini Nur (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The frigate tuna (Auxis thazard) is important to the fishing industry in West Sumatra. The increasing demand for frigate tuna causes this fish to continue to be exploited. Exploitation carried out continuously can reduce frigate tuna production, so research needs to be done. The research was conducted to: (1) Know the growth pattern and factor condition of frigate tuna (A. thazard) in West Sumatra waters; (2) Know the reproductive biology of frigate tuna (A. thazard). Samples were collected from fishermen's catch in the waters of West Sumatra. Random sampling was conducted, and samples were measured for length and weight, followed by dissection to ascertain sex ratio, gonadal maturity level, gonadal maturity index, and fecundity. The results indicated that the fish's length ranged from 350 to 475 mm, with an average of 401.48 mm, and their weight ranged from 408 to 1,339 grams, with an average of 755.8 grams. The growth pattern is identified as positive allometric (b>3), indicating that weight gain surpasses length increases. The condition factor is in stable condition with an average of 1.24. The sex ratio is in an unbalanced condition with a ratio of males and females of 0.9: 1. The level of gonad maturity obtained is GML III and GML IV. The gonad maturity index of male fish ranged from 1.71 to 3.04 and female fish from 1.28 to 2.50. Estimated fecundity ranged from 261,468 to 2,775,590 grains. Based on several factors included in this study, the reproductive biology of frigate tuna in the waters of West Sumatra is favorable.